Interior of the Aurora College Library, Yellowknife/North Slave Campus ... - Campbell, Sandy (University of Alberta Library, 2015)
This library in Yellowknife is one of several the network Aurora College libraries. In addition to the collections area in the image, the library also has a computer lab. ...